(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
The present paper studies the problems that encounter the business firms when do not apply innovations according to the thesis developed by Schumpeter. Likewise, the Hannan’s thesis about organizational ecology is exposed. The paper concludes with Altman’s model about measuring the financial fitness of companies.